Synthesis and Characterization of Some New Metals Complexes of [N-(4-Nitrobenzoyl Amino)-Thioxomethyl] Phenylalanine - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
A new ligand [N-(4-nitrobenzoylamino)-thioxomethyl] phenylalanine is synthesized by reaction of 4-nitrobenzoyl isothiocyanate with phenylalanine (1:1). It is characterized by micro elemental analysis (C.H.N.S.), FT-IR, (UV-Vis) and 1H and 13CNMR spectra. Some metals ions complexes of this ligand were prepared and characterized by FT-IR, UV-Visible spectra, conductivity measurements, magnetic susceptibility and atomic absorption. From results obtained, the following formula [M(NBA)2] where M2+ = Mn, Co, Ni, Cu, Zn, Pd, Cd and Hg, the proposed molecular structure for these complexes as tetrahedral geometry, except copper and palladium complexes are have square planer geometry.